Respostas
respondido por:
1
Aqui amigo:
3x + 3y = 21
2x - y = 5
y = 5 - 2x
3x + 3(5 - 2x) = 21
3x + 15 - 6x = 21
-3x = 21 - 15
-3x = 6
x = 6 ÷ (-3)
x = -2
y = 5 - 2x
y = 5 - 2(-2)
y = 5 - (-4)
y = 5 + 4
y = 9
S = {-2, 9}
Espero ter ajudado!
3x + 3y = 21
2x - y = 5
y = 5 - 2x
3x + 3(5 - 2x) = 21
3x + 15 - 6x = 21
-3x = 21 - 15
-3x = 6
x = 6 ÷ (-3)
x = -2
y = 5 - 2x
y = 5 - 2(-2)
y = 5 - (-4)
y = 5 + 4
y = 9
S = {-2, 9}
Espero ter ajudado!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás